A Development of Active learning management for Techer of Small Schools , Uttaradit Primary Education Service Area Office 2 - พิชัยคำ จริยา; Khrootmuang, Chalayuth; Chueamueangphan, Bunchong; Tabseesode, Issara; UdLert, Khachaporn; Kirdmalai, Benjamas; Juntranusorn, Wanissa (Journal for Developing the Social and Community, 2024)
The aims of this research were; 1) to develop the innovations of the active learning for teachers in small schools in the Uttaradit Primary Education Service Area Office 2; 2) to studysmall-school teachers’ active-learning management skillsin the Uttaradit Primary Education Service Area Office 2and; 3) to evaluate the active-learning-managementsatisfaction of the Uttaradit Primary Education Service Area Office 2’s small-school teachers. Research participants were small-school teachers in eight schools in Uttaradit Primary Education Service Area Office 2 whichconsented to participate this research project. The tools of this studywere active-learning-management handbooks, active-learning-management observation fieldnotes, active-learning-management evaluation forms, and satisfaction questionnaires. The statistic of this study involved frequency, percentage, average, and standard deviation including qualitative data. This study found; 1) the development of active-learning innovations (the active-learning-workshop training set for teachers and the supervision handbooks for active-learning management)which appropriated to develop teachers’ learning-management skills; 2) the study of teachers’ active-learning-management skills which 100% of participant teachers were able to design active-learning lessons to enhance their learners’ reading, writing, and communicating skills. This research also found that 85% of participant teachersfrom all selected schools were able to design active-learning activities. The evaluation result of their teaching-lessons plan was in the very good level(µ = 4.82 and r=0.35). and the evaluation result of their active-classroom implementation was in the practice level 3) The result of participant teachers’ active-learning-management satisfaction was also in the good level (µ = 4.38 and r=0.57).